Longitudinal links between childhood peer acceptance and the neural correlates of sharing - Will, Geert‐Jan (Dev Sci, 2016)
Childhood peer acceptance is associated with high levels of prosocial behavior and advanced perspective taking skills. Yet, the neurobiological mechanisms underlying these associations have not been studied. This functional magnetic resonance imaging study examined the neural correlates of sharing decisions in a group of adolescents who had a stable accepted status (n = 27) and a group who had a chronic rejected status (n = 19) across six elementary school grades. Both groups of adolescents played three allocation games in which they could share money with strangers with varying costs and profits to them and the other person. Stably accepted adolescents were more likely to share their money with unknown others than chronically rejected adolescents when sharing was not costly. Neuroimaging analyses showed that stably accepted adolescents, compared to chronically rejected adolescents, exhibited higher levels of activation in the temporo‐parietal junction, posterior superior temporal sulcus, temporal pole, pre‐supplementary motor area, and anterior insula during costly sharing decisions. These findings demonstrate that stable peer acceptance across childhood is associated with heightened activity in brain regions previously linked to perspective taking and the detection of social norm violations during adolescence, and thereby provide insight into processes underlying the widely established links between peer acceptance and prosocial behavior.